PENGARUH KEPEMIMPINAN DEMOKRATIS TERHADAP LOYALITAS PERAWAT PADA RUMAH SAKIT UMUM DAERAH (RSUD) KOTA SAWAHLUNTO - Serlie Putri Rianti; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research was done at On Regional General Hospital Sawahlunto. With the aim to identify and analyze the influence of the Democratic Leadership Influence Loyalty Nurses At General Hospital Sawahlunto. The population in this study were nurses at the General Hospital Sawahlunto as many as 119 people. The sample in this study was set at 83 nurses are civil servants. and data processing using simple linear regression analysis using SPSS. Based on the test results if the data using simple linear regression can be drawn some conclusions, namely: Chairman of the Regional General Hospital Sawahlunto already implementing demokratis. So seen behavior of each indicator shows the still low leadership in creating a good relationship with a subordinate , Loyalty nurses Regional General Hospital Sawahlunto is running in accordance with the wish of the General Hospital Sawahlunto. But seen from each of the indicators obedience or adherence, responsibility, dedication, and kejujuran.Indikator adherence or compliance is still low. Hypothesis test showed the presence of significant influence on loyalty nurse at General Hospital Sawahlunto. So, when viewed from the hypothesis test leading indicators in creating a good relationship with a subordinate and adherence or compliance is still low.Keyword: Democratic Leadership And Loyalty Nurses